The racial gap in entrepreneurship and opportunities inside established firms - Yang, Tiantian; Kacperczyk, Olenka (Strategic Management Journal, 2024)
Abstract Research Summary Racial disparities in entrepreneurship have been widely discussed in the literature, with most studies focusing on mechanisms that amplify such disparities. However, less attention has been devoted to factors that promote inclusion. We propose that intrapreneurship—launching and operating new ventures inside established organizations—represents a more inclusive entrepreneurial pathway than entrepreneurship involving a standalone venture. We predict that relative to White employees, Black employees will (1) be more likely to engage in intrapreneurship than entrepreneurship and (2) achieve greater financial performance as founders of internal ventures than standalone ventures. Using data on a representative sample of American new business founders in 2005, we found evidence for our theory. Our study highlights the importance of intrapreneurship in leveling the playing field for racial minorities pursuing entrepreneurial activities. Managerial Summary Despite the persistent inequalities in the representation of racial minorities in entrepreneurship, how to make the entrepreneurial path more inclusive remains less well understood. In this study, we find that intrapreneurship—or launching and running a new venture within an already established firm—holds the potential to offering a more inclusive route to entrepreneurship, compared to the traditional way of starting a standalone business. Using data from a representative sample of American business founders in 2005, we find that Black employees are more likely to take the intrapreneurship route rather than starting their own independent businesses. We also find that, conditional on founding a new venture, Blacks are more likely to achieve financial success as intrapreneurs than entrepreneurs. Finally, when discrimination is more prevalent and other indicators of quality are lacking, the gaps in founding rates and new‐venture performance between Blacks and Whites are less likely to widen in intrapreneurship compared to standalone entrepreneurship. Overall, these findings have important implications for practices that can help address the racial disparities we see in entrepreneurship.